Hepatoprotective, immunomodulatory and antibacterial effects of selected Malaysian medicinal plant extracts / Mohammed Abdullah Mahdi Alshawsh - Mohammed Abdullah, Mahdi Alshawsh (2013)
Orthosiphon stamineus Benth and Morinda citrifolia L. are considered an important traditional folk medicine and commonly used in Malaysia for treating many diseases. In this study, the ethanol extracts of O. stamineus and M. citrifolia were evaluated for their hepatoprotective and antioxidant activities; in vivo against thioacetamide-induced liver cirrhosis in rats and in vitro against H2O2-induced hepatotoxicity in WRL-68 liver cell line, as well as to investigate their immunomodulatory and antibacterial effects. Orthosiphon stamineus and Morinda citrifolia were evaluated for their antioxidant activities using DPPH, ABTS and FRAP. In addition the phenolic and flavonoids contents were determined. Seven groups of adult SD rats were used in the hepatoprotective experiment. Group 1 as normal control group, while groups 2 to 7 were injected intraperitoneally with 200 mg/kg of thioacetamide (TAA) thrice weekly for two months and orally administered respectively with 10 % Tween 20, 50 mg/kg silymarin, 200 mg/kg and 100 mg/kg ethanol extract of O. stamineus and M. citrifolia daily for two months. The hepatoprotective activity was evaluated using the following parameters; body and liver weight, serum liver biochemical markers, liver gross morphology and histopathology, as well as endogenous antioxidant markers. Furthermore, the liver fibrosis related genes namely; TGFβ1, MMP2, TIMP1 and Coll α were estimated for the change in gene expression levels using RT-PCR. In addition, the ethanol crude extracts of O. stamineus and M. citrifolia and their isolated fractions were investigated against H2O2-induced hepatotoxicity in WRL-68 liver cell line and the percentage of cell viability using MTT assay and the antioxidant level markers were assessed. The immunomodulatory potential of the extracts were investigated by MTT assay against human peripheral blood mononuclear cells (PBMCs), while the antibacterial activity was investigated by disc diffusion and determination of minimum iii inhibitory concentration (MIC) against four Gram-positive and Gram-negative bacterial strains. Finally, LC-MS was used for identification of the active constituents of the fractions that proved to have hepatoprotective activity. Orthosiphon stamineus exhibited significant free radical scavenging activity with DPPH (IC50 21.4 μg/ml), at the same time, showed high total phenolic and flavonoidal contents. In animal experiments, the hepatotoxic group showed a coarse granulation on the liver surface when compared to the smooth aspect observed on the liver surface of normal and treatment groups. Histopathological study confirmed the result. Moreover, there was a significant (P < 0.05) increase in serum liver biochemical parameters (ALT, AST, ALP and bilirubin) and the level of liver lipid peroxidation index malondialdehyde (MDA), accompanied by a significant decrease in the level of total protein, albumin, catalase, superoxide dismutase and glutathione peroxidase in the TAA control group comparing with normal group. The 200 mg/kg treatment groups of both plants significantly restored the elevated liver function enzymes and antioxidant parameters near to normal and significantly down-regulated the expression of the liver fibrosis genes. The oxidative stress by H2O2 resulted in a decrease of cell viability to 41.9 %, while pre-treatment with crude extracts of O. stamineus and M. citrifolia, as well as with fraction 3 of O. stamineus and fraction 2 of M. citrifolia were found significantly (P < 0.01) increase the cell viability to 81.1 %, 76.4 %, 95.1 % and 86.1 % respectively at concentration 100 μg/ml. The hepatoprotective and antioxidant activity could be claimed to the following flavonoids; ponkanetin, eupatorin, TMF and salvigenin that were identified in O. stamineus F3 and scopoletin and P- coumaric acid, which were identified in M. citrifolia F2. In conclusion, this study showed that O. stamineus and M. citrifolia exhibit potent antioxidant properties, immunomodulatory activity and could be an effective herbal and efficient remedy for chemical-induced hepatic cirrhosis, thus may be a highly promising candidate drugs.